High and Low Value-Added Schools. Differential Profiles of Secondary Schools in Baja California (Mexico) - Maria Castro-Morera; Adán Moisés García-Medina; Luis Horacio Pedroza-Zuñiga; Joaquín Caso-Niebla (Arizona State University, 2015)
Contextual value-added models have been serving as a tool for the development of evaluation systems based on accountability. However, the study of school's contribution after controlling for background characteristics related to the socio-cultural level of students and schools (technically called residuals) can also serve to identify and study the good educational practices of those centers that promote student performance more beyond that expected for their socio-cultural conditions starting. The aim of this article is differentially describe the characteristics of these secondary schools in the state of Baja California (Mexico). For this we have used the information from the instruments that belong to the Estrategia Evaluativa Integral for 2010 and 2011. The results show that schools that promote beyond the expected performance of their students are characterized among students there are higher levels democratic coexistence, sense of belonging, self-reliance and school expectations; likewise, Math teachers give them more support when students have doubts and offer them a richer feedback. Surprisingly, high and low value-add schools do not differ in the type of activities that teachers do with students of low achievement. This article is a good illustration of the many uses that can be given to the contextual value-added models.